Precarious labour in Mpumalanga, South Africa: A case study of informally employed day labourers in Mbombela and Emalahleni. Issue 244 (22nd February 2022) - Blaauw, Derick; Pretorius, Anmar; Schenck, Catherina; Matthee, Marianne
Abstract: Precarious employment is becoming more prevalent again in the developed world while being widespread in developing economies. Day labour is precarious wage work that is emerging and re‐emerging in the global North and South. Within the global South context, we explore the socio‐economic and labour market outcomes of day labourers in Mpumalanga. A comparable multi‐case study research design reveals day labourers' precarious existence: low and uncertain incomes, struggle to provide for dependents, low levels of subjective well‐being and structural vulnerability. The results reflect differences between a more diversified economy (Mbombela) and one subject to the mining industry's boom and bust cycles (Emalahleni). Social policy must be reconsidered to adhere to the South African government's developmental state vision.